Proliferation of open government initiatives and systems - Kok, Ayse 1979 (Advances in Electronic Government, Digital, Divide, and Regional Development (AEGDDRD) Book Series, 2018)
"This book analyzes the interaction between Internet culture and the bureaucratic culture of secrecy. It explores how the collection of data enables the acquisition of a solid body of evidence leads to mapping initiatives across case studies and developing a common set of metrics to consistently assess impact and value creation within and across countries"